The Multiliteracies Learning Environment as Decolonial Nexus: Designing for Decolonial Teaching in a Literacies Course at a South African University. (2nd January 2020) - Andrews, Grant; Prozesky, Maria; Fouché, Ilse
Abstract: In higher education institutions in South Africa, educators working in the fields of language and academic literacy need to be sensitive and responsive to the linguistic and cultural diversity of the student body, and traditional pedagogical approaches are often inappropriate to meet the needs of students and of the wider call to decolonise higher education. As a group of lecturers working at the University of the Witwatersrand's School of Education in Johannesburg, South Africa, we worked to respond to this context by designing a literacies course that was underpinned by a decolonial and social practices approach to literacy. Using critical reflection as a research method, this article traces our theoretical grounding in designing this course, including New Literacies Studies (NLS), community cultural wealth, and theories in indigenous studies, such as cultural interface theory. This article further demonstrates how we applied this theoretical framework through introducing practical activities that could be used to develop situated literacies and that tapped into the community cultural wealth that students bring to the classroom. We discuss four formative and summative assessment elements that were central to the course, namely online assessments, portfolio tasks, an argumentative essay, and what we termed the triad project, to illustrate how the decolonial approach informed our curriculum design and pedagogy. Our approach allowed us to explore new forms of assessment which opened space for students' home languages, literacy practices, and identities to become valuable elements of teaching and learning.